2002
DOI: 10.1051/apido:2002017
|View full text |Cite
|
Sign up to set email alerts
|

Critical temperatures for survival of brood and adult workers of the giant honeybee, Apis dorsata (Hymenoptera: Apidae)

Abstract: -Capped brood ( capped within 36 h) and adult workers of Apis dorsata were removed from naturally occurring colonies and kept incubated in laboratory hoarding cages at constant temperatures ranging from 26 to 45 o C to study mortality, survivorship, and water and syrup consumption. Capped brood died at temperatures above 36 o C. Below 30 o C adults tended to emerge deformed. Low temperatures delayed development. The optimal temperature for complete emergence of healthy adult workers was 34 o C. Adult workers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
1
23
0
4
Order By: Relevance
“…Groups of 100 newly emerged Africanized honey bees, collected from three different colonies in an apiary in Ribeirão Preto, SP, Brazil, were mixed and placed into hoarding cages (Kulincevic and Rothenbuhler, 1973;Mardan and Kevan, 2002). The cages with bees were maintained in an incubator, with no light, at 30ºC and about 70% relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Groups of 100 newly emerged Africanized honey bees, collected from three different colonies in an apiary in Ribeirão Preto, SP, Brazil, were mixed and placed into hoarding cages (Kulincevic and Rothenbuhler, 1973;Mardan and Kevan, 2002). The cages with bees were maintained in an incubator, with no light, at 30ºC and about 70% relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Heat stress-We exposed bees to 42°C in an incubator; colonies typically maintain their hives at approximately 34°C by behavioral thermoregulation, and it has been reported (Mardan and Kevan, 2002) that bees kept at 42°C showed decreased longevity. Bees were kept at 42°C until they died.…”
Section: Stress Testsmentioning
confidence: 99%
“…Lindauer (1956), Morse and Benton (1967), Reddy (1980) and Seeley et al (1982) also found the similar, non disturbed nesting sites of A. dorsata throughout South and South-east Asia. Mardan (1989) and Crane (1990) explained the nest site chosen by A. dorsata swarms for nesting was usually not directly exposed to wind currents and partially sheltered. Swarms closer to the old nest sites got first opportunity to occupy the protective nest sites and also exploited natural and cultivated flora for their survival, growth and development.…”
Section: Discussionmentioning
confidence: 99%